1997
DOI: 10.1007/s002239900205
|View full text |Cite
|
Sign up to set email alerts
|

Osteoporosis and Bone Mineral Metabolism Disorders in Cirrhotic Patients Referred for Orthotopic Liver Transplantation

Abstract: The purpose of this study was to determine the prevalence of osteoporosis, to estimate the bone turnover and hormonal status, and to identify the factors associated with bone disease in patients with end-stage liver disease who were referred for orthotopic liver transplantation. A prospective study was performed on 58 cirrhotic patients (6 with primary biliary cirrhosis, 14 with alcoholic cirrhosis, and 38 with posthepatitic cirrhosis), who were referred for orthotopic liver transplantation. Patients, excludin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
108
2
3

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 198 publications
(128 citation statements)
references
References 24 publications
15
108
2
3
Order By: Relevance
“…This finding is similar to the observations of other studies [15,20]. In our series, 61 patients with CLD had vitamin D levels less than 80 nmol/l, but only in 6 (9.8%) patients the serum PTH level was increased ([6.8 pmol/l).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This finding is similar to the observations of other studies [15,20]. In our series, 61 patients with CLD had vitamin D levels less than 80 nmol/l, but only in 6 (9.8%) patients the serum PTH level was increased ([6.8 pmol/l).…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have shown inconsistent results about the correlation between serum vitamin D level and the severity of liver dysfunction. Our results are in line [3,19] with some studies, and in contradiction to some other studies [16,20]. Our study also showed a significant correlation between low serum vitamin D level and markers of liver function insufficiency including coagulopathy, hypoalbuminemia, hyperbilirubinemia, and thrombocytopenia, in agreement with other studies [21][22][23].…”
Section: Discussionsupporting
confidence: 82%
“…51 There have been relatively few studies of changes in sex hormone status following liver transplantation and those that exist are confined to men. An increase in free testosterone following transplantation has been a common finding in these studies, although recovery to normal levels is not achieved in all patients.…”
Section: Hypogonadismmentioning
confidence: 99%
“…Although this may occur in patients with chronic liver disease, it is rare. 52 Conversely vitamin D insufficiency, in which lesser degrees of deficiency result in secondary hyperparathyroidism and bone loss, 53 is commonly associated with chronic liver disease 50,51,54,55 and may contribute to post-transplantation osteoporosis. Prospective studies indicate that serum 25-hydroxyvitamin D levels, which reflect vitamin D status, tend to increase with time after transplantation, 15,23,33 and in the study of Feller et al 27 significantly higher serum 25-hydroxyvitamin D levels were noted at a mean of 85 months follow-up than prior to transplantation; however, serum 1,25-dihydroxyvitamin D levels, which were normal at baseline, did not change during the follow-up period.…”
Section: Vitamin D Deficiency/insufficiencymentioning
confidence: 99%
See 1 more Smart Citation